Catalogue of the type specimens in the fish collection of the National Zoological Museum, Institute of Zoology, Chinese Academy of Sciences, Beijing, China - Ye, Enqi; Xing, Yingchun; Zhang, Chunguang; Zhao, Yahui (Zootaxa, 2015)
A checklist of type specimens housed in the National Zoological Museum, Institute of Zoology, Chinese Academy of Sciences, Beijing, is presented for research and scientific communication. Included are 80 holotypes, 1 lectotype, 1 neotype, 402 paratypes and 17 syntypes of 99 species belonging to 28 families and 12 orders. With 60 species, Cypriniformes has the largest representation. All of the specimens were collected in China and neighboring countries in the past 90 years.